Do we need a new educational standard for higher medical education? - Felix A. Blyakhman; Valery A. Teleshev (Moscow Polytechnic University, 2022)
The authors strongly argue that the role of fundamental knowledge in the course of physicians' training is evidently underestimated. This paper addresses to a wide readership auditory, and its aim is an invitation for a comprehensive discussion of the future of higher medical education.